Lysozyme-based spray for treatment of radiotherapy-induced oral mucositis - Zdenka Gojković; Jelena Rožić; Nataša Gašpar; Aziz Šukalo; Meliha Mehić; Amna Tanović Avdić; Una Glamočlija (Exploration of Drug Science)
Aim: The aim of this study was to examine the effectiveness and safety of lysozyme-based spray in the treatment of oral mucositis in patients undergoing head and neck radiotherapy. Methods: A prospective, open-label study was conducted on patients with ulcerative inflammation of the oral cavity and pharynx mucous membranes clinically assessed for oral mucositis according to the World Health Organization (WHO) Oral Toxicity Scale. Patients were randomly divided into a lysozyme group (using a spray containing lysozyme + cetylpyridinium + lidocaine) and a control group (using a compounded preparation containing gentamicin + dexamethasone + lidocaine). The efficacy and safety of therapy were evaluated on the baseline and three follow-up visits (7, 14, and 21 days after the baseline visit). Results: The total number of participants was 56, of which 26 were in lysozyme and 30 in the control group. The efficacy parameters were similar between the groups and there was no deterioration of symptoms during the follow-up period of 21 days. A significantly lower pain intensity when eating solid food was observed after 21 days in lysozyme compared to the control group. No adverse reactions were observed. Conclusions: This study showed the efficacy and safety of lysozyme-based spray for treating radiotherapy-induced oral mucositis. The availability of new treatment options based on lysozyme, a natural enzybiotic present in the saliva of healthy subjects, could bring added value to the treatment of oral mucositis and the prevention of its complications. However, a larger randomized, blinded study is needed to confirm our results [the study was registered at the Agency for Medicinal Products and Medical Devices of Bosnia and Herzegovina (https://klinicka.almbih.gov.ba/pages/klinicka-registar-javni) under the protocol number LCS-OM-01].